A Numerical Stability Study on Truss Structures - Qian, Yuan-yao; Batoz, Jean-Louis (European Journal of Computational Mechanics, 1992)
This paper, which presents a numerical study on non-linear stability problems of truss structures, concentrates on three main parts. First, the derivative of the tangential stiffness matrix is used to give the stability analysis with direct calculation of the critical points and the branch-switching function. And then a quadratically convergent pathfollowing algorithm is obtained. Compared with the classical arc-length methods, it is more efficient in fast convergence and saving CPU time. Finally it studies four geometrically nonlinear problems in details.